Simulation of solar cooling system - Goh, Dennis Kim Lai. (2010)
As our climate becomes hotter due to global warming, and the demands for air conditioning rises, it is important use an alternative solution to meet our demands and at the same time to reduce the amount of fossil fuel consumption and harmful emissions to the environment. Using solar energy can be a solution to that demand, as solar radiation is an abundant source of clean energy which goes to waste every day.